A retrospective study of Babesia macropus associated with morbidity and mortality in eastern grey kangaroos (Macropus giganteus) and agile wallabies (Macropus agilis). Issue 2 (August 2015) - Donahoe, Shannon L.; Peacock, Christopher S.; Choo, Ace Y.L.; Cook, Roger W.; O'Donoghue, Peter; Crameri, Sandra; Vogelnest, Larry; Gordon, Anita N.; Scott, Jenni L.; Rose, Karrie
Highlights Detailed description of novel Babesia infection causing mortality in macropods. First report of this infection in agile wallabies. Information on the geographical incidence of this disease in the eastern states of Australia. Comprehensive review of the clinical signs and pathology of the disease.